Malaysian Popular Music and Social Cohesion: A Focus Group Study Conducted in Kuching, Kota Kinabalu and Klang Valley - Adil Johan; Shazlin Amir Hamzah (Kajian Malaysia, 2019)
In March and April 2019, a total of 12 focus groups were conducted in Kota Kinabalu, Kuching and Klang Valley. The study interviewed informants about their everyday experiences and preferences in consuming popular music. It also sought to determine specific popular and patriotic songs, made and circulated within Malaysia from the 1960s to 2000s, that garnered a wide appeal and fostered a sense of collective Malaysian identity amongst the informants. The informants were divided into four demographic groups in each location: (1) youths (aged 19 to 39), (2) business owners or entrepreneurs (any age), (3) professionals (any age), and (4) arts practitioners and musicians. This research note provides a brief review of the existing studies on Malaysian popular music that inform the study. However, despite the significant amount of research on Malaysian popular music from the 1980s until the present day, there has yet to be a study that considers the responses and attitudes of Malaysian citizens – as music listeners and consumers – toward Malaysian popular music. More so, the study hopes to move beyond critical approaches that only focus on contestations between music producers and performers with the authority-defined structures and policies of the nationstate. We propose an epistemological shift to focus on the musical preferences and everyday experiences of Malaysians as well as music producers and performers to determine if consuming popular music provides an unofficial and everyday- experienced space for social cohesion, integration and collective flourishing amidst a diverse multicultural nation.